Methods and Means of Improving the Safety of Working Conditions in Cotton Gins - Muqimov., N.; Yuldosheva, O. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the personal protective equipment used by employees of ginneries and ways to increase their efficiency.